Implikasi Isbat Nikah Terhadap Pemulihan Status Sosial Pada Praktik Pernikahan Anak Tidak Tercatat di Desa Banjarsari - Della Marchellina S.; Wahyu Abdul Jafar; Nency Dela Oktora; Seja Riyandani (Al-Mizan (e-Journal), 2026)
Child marriage remains a persistent issue in Indonesia despite the enactment of Law Number 16 of 2019, which sets the minimum marriage age at 19 years. Previous studies have predominantly focused on the legal status of unregistered marriage and child protection issues, while limited attention has been given to the role of isbat nikah in restoring the social status of families involved in underage unregistered marriages. This study aims to analyze the implications of isbat nikah on social reintegration within rural communities, particularly in Banjarsari Village. This research employs a qualitative case study approach, using interviews, observations, and documentation with families who obtained marriage ratification (isbat nikah) decisions and with village officials. The findings reveal that isbat nikah functions not only as a legal mechanism for administrative recognition but also as an instrument of social reintegration. Legal recognition through court decisions reduces social stigma, strengthens community acceptance, and improves access to civil administration and public services. The study highlights the novelty of viewing isbat nikah not merely as a formal legal procedure but as a socio-legal instrument that restores both legal and social status for families affected by child marriage practices.